Designing Block Copolymers for Nanolithography using Mesoscale Modeling: Line-Space Graphoepitaxy. Issue 25 (2nd February 2016) - Ginzburg, Valeriy V.; Hustad, Phillip D.; Millward, Dan B.; Trefonas, Peter
ABSTRACT: Directed self-assembly (DSA) of block copolymers is a promising alternative nanolithographic technology aimed at producing sub-40 nm patterns. One important opportunity for DSA is the creation of periodic arrays of lines and spaces. The two most common methods for line-space applications are chemoepitaxy (typically using a lamella-forming PS-b-PMMA diblock) and graphoepitaxy (typically using cylinder-forming block copolymers with a Si-containing minority block). Mesoscale modeling, such as Self-Consistent Field Theory (SCFT), has by now become an important tool in formulation screening and predicting polymer morphologies and defect types and probabilities. Here, we use SCFT to study the morphology of cylinder-forming PS-b-PDMS diblocks in rectangular trenches with grafted PS-brushes. The targeted morphology is 2 cylinders per trench (3X multiplication). We compute phase diagrams and determine equilibrium morphologies as a function of brush thickness and guiding weir height. Using those equilibrium morphologies as starting points, we also compute structures and free energies of typical defects, including dislocation and disclination dipoles, broken lines, and bridges. The predicted defect structures and probabilities are in a reasonable qualitative agreement with recent experimental results.